2019
DOI: 10.1016/j.cell.2019.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy-Independent Functions of the Autophagy Machinery

Abstract: Macroautophagy (herein referred to as autophagy) is an evolutionary ancient mechanism that culminates with the lysosomal degradation of superfluous or potentially dangerous cytosolic entities. Over the past 2 decades, the molecular mechanisms underlying several variants of autophagy have been characterized in detail. Accumulating evidence suggests that most, if not all, components of the molecular machinery for autophagy also mediate autophagy-independent functions. Here, we discuss emerging data on the non-au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
536
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 695 publications
(549 citation statements)
references
References 146 publications
8
536
1
4
Order By: Relevance
“…Beclin-1 is required in the pre-autophagosomal structure, and thus, its expression is associated with autophagosome activity. P62 is an autophagic degradation substrate, and a widely used marker of autophagic flux (Cirone et al, 2019;Galluzzi and Green, 2019). SCI recovery has been associated with autophagy (Kanno et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Beclin-1 is required in the pre-autophagosomal structure, and thus, its expression is associated with autophagosome activity. P62 is an autophagic degradation substrate, and a widely used marker of autophagic flux (Cirone et al, 2019;Galluzzi and Green, 2019). SCI recovery has been associated with autophagy (Kanno et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that the deficiency in cell migration does not arise from the progression and differentiation of the stem cell lineage. It has been recently reported that Atg5 deletion may produce an autophagy-independent effect (Galluzzi and Green, 2019). To verify this possibility, we genetically impaired the expression of Atg12, another essential autophagyrelated gene, using CRISPR/Cas9 technology.…”
Section: The Suppression Of Autophagy Hampers Cell Migration and Leadmentioning
confidence: 98%
“…Nevertheless, depleting the essential autophagic vesicle protein ATG5 impairs MOPV, LASV, and JUNV replication [86][87][88], indicating that both OW and NW arenaviruses may utilize components of the autophagy pathway to aid in replication. While ATG5 is the key component in autophagy, there is increasing evidence that ATG5 also plays roles in non-autophagy processes, including negative regulation of RIG-I or MDA5 [89][90][91]. Thus, future studies are required to define if ATG5 is directly involved in arenavirus replication.…”
Section: Arenavirus Subversion Of Other Host Antiviral Defensesmentioning
confidence: 99%